Seeing through porous media: An experimental study for unveiling interstitial flows. Issue 3 (16th January 2018) - Rubol, Simonetta; Tonina, Daniele; Vincent, Lionel; Sohm, Jill A.; Basham, William; Budwig, Ralph; Savalia, Pratixa; Kanso, Eva; Capone, Douglas G.; Nealson, Kenneth H.
Abstract: We describe a novel inexpensive method, utilizing particle image velocimetry (PIV) and refractive index‐matching (RIM) for visualizing and quantifying the flow field within bio‐amended porous media. To date, this technique has been limited to idealized particles, whose refractive index does not match that of fresh water and thus requires specialized and often toxic or hazardous fluids. Here, we use irregularly shaped grains made of hydrogel as the solid matrix and water as the fluid. The advantage of using water is that it provides, for the first time, the opportunity to study both hydraulic and biological processes, which typically occur in soils and streambeds. By using RIM coupled with PIV (RIM‐PIV), we measured the interstitial flow field within a cell packed with granular material consisting of hydrogel grains in a size range of 1–8 mm, both in the presence and in the absence of Sinorhizobium meliloti bacteria (strain Rm8530). We also performed experiments with fluorescent tracer (fluorescein) and fluorescent microbes ( Shewanella GPF MR‐1 ) to test the capability of visualizing solute transport and microbial movements. Results showed that the RIM‐PIV can measure the flow field for both biofilm‐free and biofilm‐covered hydrogel grains. The fluorescent tracer injection showed the ability to visualize both physical (concave surfaces and eddies) and biological (biofilms) transient storage zones, whereas the fluorescent microbe treatment showed the ability to track microbial movements within fluids. We conclude that the proposed methodology is a promising tool to visualize and quantify biofilm attachment, growth, and detachment in a system closer to natural conditions than a 2D flow cell experiment.